Oscillation of Second-Order Neutral Functional Differential Equations with Mixed Nonlinearities - Shurong Sun; Tongxing Li; Zhenlai Han; Yibing Sun (Abstract and Applied Analysis)
We study the following second-order neutral functional differential equation with mixed nonlinearities (r(t)|(u(t)+p(t)u(t-σ))'|α-1(u(t)+p(t)u(t-σ))′)′+q0(t)|u(τ0(t))|α-1u(τ0(t))+q1(t)|u(τ1(t))|β-1u(τ1(t))+q2(t)|u(τ2(t))|γ-1u(τ2(t))=0, where γ>α>β>0, ∫t0∞(1/r1/α(t))dt<∞. Oscillation results for the equation are established which improve the results obtained by Sun and Meng (2006), Xu and Meng (2006), Sun and Meng (2009), and Han et al. (2010).